The Influence of Compensation Alignment and Placement on the Performance of Public Works Employees in a Regional Authority - Kessi, Andi Muhammad Fara; Tajuddin, Imran (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The aim of this research is to determine whether there is an influence of compensation and work placement on employee performance in a regional authority. The study's population consisted of 39 employees, and the research sample used a saturated sampling method. This research employs a quantitative approach, utilizing data analysis methods that include research instrument tests, validity and reliability tests, descriptive analysis, inferential analysis, multiple linear regression analysis, coefficient of determination (R²), hypothesis testing, partial tests, t-tests, and classical assumption tests such as normality, multicollinearity, and heteroscedasticity. The results indicate a significant positive influence of compensation on employee performance at the Public Works Department of the regional authority. However, there was no significant positive effect of placement on employee performance in the same department. For future research, it is suggested to explore additional factors influencing employee performance, such as job satisfaction and organizational culture, as well as to include a larger sample size for more robust findings.